ҚОРШАҒАН ОРТАНЫ ҚОРҒАУ САЛАСЫНДАҒЫ МЕМЛЕКЕТТІК БАҚЫЛАУДЫҢ ҚҰҚЫҚТЫҚ НЕГІЗДЕРІ (Journal of actual problems of jurisprudence, 2019)
In this article author presents ecology condition in Republic of Kazakhstan state control bases, types and methods of it’simprovement.